The Effect of Mother's Knowledge about Stunting Prevention on Incidents of Stunting in Gunung Leutik Village, Ciparay Subdistrict, Bandung District - Ruhayati, Ratih; Farah, Laila (Rifa'Institute, 2025)
Stunting is a condition in which a child experiences growth disturbances, resulting in a height that is not appropriate for their age. This condition is caused by chronic nutritional problems, namely a lack of nutrient intake over a long period, starting from pregnancy. In addition, it is also exacerbated by mothers’ lack of knowledge regarding stunting prevention. Ciparay Subdistrict is the second priority area in Bandung District with a relatively high stunting rate of 25%. The purpose of this study was to determine the effect of mothers' knowledge about stunting prevention on the incidence of stunting in Gunung Leutik Village, Ciparay Subdistrict, Bandung District. The research method used was a quantitative descriptive approach with simple linear regression analysis. The population consisted of 149 mothers of toddlers, and the sample included 60 respondents selected using accidental sampling. The results of the study with simple linear regression analysis produced a regression coefficient (b) of -0.135 and an intercept (a) of 1.638, resulting in the regression equation Y = 1.638 – 0.135X. It can be concluded that every one-level increase in knowledge reduces the incidence of stunting by 0.135. In other words, the higher the mother's knowledge about stunting prevention, the lower the incidence of stunting. Based on these results, it is expected that mothers of toddlers will improve their knowledge regarding stunting prevention